Shear Strength Parameters of Soil-Geosynthetic Interfaces Under Low Confining Pressure Using a Tilting Table. Issue 4 (1st January 2002) - Burke, C.; Matsushima, K.; Mohri, Y.; Ling, H.I.
Abstract : Tilting table tests are typically used to determine the friction angle between soils and structures. A procedure is presented to determine both the adhesion and frictional properties of soil-geosynthetic interfaces under very low confining pressures using a tilting table test. A simple tilting table device was developed and a series of tests were conducted on three different types of sand in contact with smooth and textured geomembranes under dry and moist conditions. The study showed the relevance of the proposed procedure and device especially when residual state is concerned.